Public Impact. Citizen influence in local government in Iceland - Gunnar Helgi Kristinsson (Icelandic Review of Politics & Administration, 2009)
Considering its importance in democratic theory, public impact on public policy is a strangely neglected theme in political science. The main theoretical traditions in political science, in fact, seem sceptical of claims that the public can influence public policy in a systematic manner. The present article is an attempt to consider the ways in which public impact may be studied and evaluated through a study of citizen influence in planning and environmental issues in Icelandic local government. The results indicate - even if only tentatively - that the impact of the citizens is greater than would be expected on the basis of the main theoretical traditions in political science.(The article is part of a larger research project supported by the Icelandic Centre for Research, the University of Iceland Research Fund, Association of Local Authorities in Iceland, Landsbanki Íslands and Orkuveita Reykjavíkur.)